Parenting Styles, Self-esteem and Gender on Eating Behavior among Primary School Pupils in Nigeria - Ehondor , Esohe G.; Adetayo, Adenike O.; Uye, Emmanuel E. (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2024)
Eating behavior has remained a recurring issue for parents, teachers, and the government as children move into their formal level of learning. Studies linking children's eating behavior to parenting styles and self-esteem in a semi-urban settlement in Nigeria are lacking. Therefore, this study examined the influence of parenting styles, self-esteem, and gender on eating behavior among primary school pupils in Lagos, Nigeria. A cross-sectional survey design was adopted while validated questionnaires were used to gather data from 198 parents of pupils of four randomly selected primary schools. Data were analyzed using zero-order correlation, a t-test of independent samples, and a 2 x 2 ANOVA. Four hypotheses were tested and accepted at p <.05 level of significance. The results showed that parenting styles and self-esteem significantly influenced eating behavior among primary school pupils [t(136) = 2.573, p <.05]. Also, the result indicated that parenting styles and self-esteem had significant interaction effects on eating behavior [F(2,134) = 4.732, p <.05]. Finally, gender-differentiated eating behavior among study participants [t (191) =-3.672, p < .05). The study concluded that parenting styles, self-esteem, and gender are strong contributors to eating behavior among study participants. The study recommended that parents, government and other stakeholders should work in synergy to improve the dietary requirements of primary school pupils to prevent malnutrition in the future.